HIV-Positive Patients’ Perceptions of Antiretroviral Therapy Adherence in Relation to Subjective Time: Imprinting, Domino Effects, and Future Shadowing - Lessard, David (J Int Assoc Provid AIDS Care, 2018)
Antiretroviral treatment adherence barriers are major concerns in HIV care. They are multiple and change over time. Considering temporality in patients’ perceptions of adherence barriers could improve adherence management. We explored how temporality manifests itself in patients’ perceptions of adherence barriers. We conducted 2 semi-structured focus groups on adherence barriers with 12 adults with HIV which were analyzed with grounded theory. A third focus group served to validate the results obtained. Three temporal categories were manifest in HIV-positive patients’ perceptions of barriers: (1) imprinting (events with lasting impacts on patients), (2) domino effects (chain of life events), and (3) future shadowing (apprehension about long-term adherence). An overarching theme, weathering (gradual erosion of abilities to adhere), traversed these categories. These temporalities explain how similar barriers may be perceived differently by patients. They could be useful to providers for adapting their interventions and improving understanding of patients’ subjective experience of adherence.